Human papillomavirus DNA and p16INK4a expression in hypopharyngeal cancer and in relation to clinical outcome, in Stockholm, Sweden. Issue 9 (September 2015) - Dalianis, Tina; Grün, Nathalie; Koch, Jana; Vlastos, Andrea; Tertipis, Nikolaos; Nordfors, Cecilia; Näsman, Anders; Wendt, Malin; Romanitan, Mircea; Bersani, Cinzia; Munck-Wikland, Eva; Ramqvist, Torbjörn
Highlights: HPV DNA and p16 positive hypopharyngeal cancer was rare in Stockholm, Sweden. HPV DNA and p16 positive hypopharyngeal cancer had not increased over the past years. Patients HPV DNA and p16 positive hypopharyngeal cancer had better clinical outcome. p16 overexpression was not a surrogate marker for HPV DNA in hypopharynx cancer. p16 overexpression did not predict better clinical outcome in hypopharynx cancer. Summary: Objectives: Hypopharyngeal cancer is a subset of head neck squamous cell carcinoma (HNSCC) with particularly poor prognosis. Human papillomavirus (HPV) is a risk factor for some HNSCC, and its presence is of prognostic value for certain subsites. However, its influence on survival in hypopharyngeal cancer has not been thoroughly investigated. Here we examine HPV DNA and p16 INK4a (p16) overexpression in relation to clinical outcome. Materials and Methods: Hypopharyngeal tumour biopsies from 82 patients diagnosed 2008–2013 were examined for presence of HPV DNA by a bead-based multiplex assay and for p16 expression by immunohistochemistry, and the obtained data compared to that acquired previously from 109 patients diagnosed 2000–2007 at the same clinic. A survival analysis was then performed on 142 patients (from both studies) treated with curative intent and a 3-year follow-up time. Results: Of the tumour biopsies 3/82 (3.7%) were HPV16 DNA and p16 positive, while 12/82 (14.6%) were p16 positive, equivalent to that in the previous study. Overall 3-year survival was significantly more favourable for patients with HPV16 DNA and p16 positive tumours as compared to survival of the other patients (86% vs. 31%, p  = 0.0185). A similar but not statistically significant trend was found for disease specific survival. Conclusion: HPV DNA and p16 positive hypopharyngeal cancer was rare and had not increased, but had a better clinical outcome as compared to other HPV-unrelated hypopharyngeal cancer. In addition, p16 overexpression was not a suitable surrogate marker for presence of HPV or for prediction of survival in this type of cancer.